Comparison of Predictability in Vault Using NK Formula and KS Formula for the Implantable Collamer Lens Surgery - Xin Zhong; Yan Li; Yuancun Li; Geng Wang; Yali Du; Mingzhi Zhang (Journal of Ophthalmology, 2024)
Background. This study aims to investigate the agreement between the NK and KS formulas in predicting the vault after implantation of an EVO-implantable collamer lens (ICL). Methods. This retrospective study included 106 eyes of 57 patients who underwent ICL-V4c implantation. Preoperative vault prediction was conducted by utilizing the NK and KS formulas, with postoperative measurements by anterior segment optical coherence tomography (AS-OCT) at one month. The analysis focused on the consistency between predicted and achieved vaults, as well as the correlation between the achieved vault and various biometric parameters. Results. The mean achieved vault was 605.25 ± 212.72 µm, which was significantly smaller than the predicted vaults of 710.08 ± 195.08 and 673.80 ± 212.76 µm, using the NK and KS formulas, respectively (P<0.05). The mean differences between the achieved vault and the predicted vault using the NK formula and KS formula were −104.82 μm (95% LoA: −600.38–391.19 μm) and −68.55 μm (95% LoA: −628.91–491.82 μm), respectively. Anterior chamber depth (ACD), vertical sulcus-to-sulcus (V-STS) diameter, and crystalline lens rise (CLR) were independent factors associated with the achieved vault (P<0.05). The two formulas showed no statistically significant difference in absolute prediction error (APE). Conclusion. The NK formula exhibited superior consistency and low predictive error compared to the KS formula in the 12.6 mm ICL group. AS-OCT measurements overestimated the predicted ICL vault, especially in the 13.2 mm ICL size selection. Relying solely on the NK or KS formulas for predicting vaults before ICL surgery is not recommended.